The abolition of bonded labour and slavery in India: from ‘Poor Law’ to a fundamental right – the gradual changes of an institution, 1843-1990 - Molfenter, Christine (2020)
This dissertation focuses on the development of policies against bonded labour and slavery in India between 1843 and the 1990s. Starting with the abolition of the slave trade by the British in 1833, the author argues that the following developments of the policies and the interpretation of the high courts of anti-slavery legislation, incrementally changed over the period of 200 years. Taking a historical institutionalist approach, this work suggests an adaptation of the theory of gradual institutional change developed by Thelen, Mahoney and Streeck and tests it to the case of the abolition of slavery in India with a particular focus on bonded labour.
Gesehen am 02.07.2020
Keywords: Indien; Graue Literatur; Hochschulschrift